COMMUNITY ORGANIZATION AND PARTICIPATION (THE ROLE OF VILLAGE COUNCIL AND PARTICIPATION IN PHYSICAL DEVELOPMENT OF PPMK AT SOUTH CIPINANG BESAR VILLAGE, DKI JAKARTA) - M. Husni Thamrin (NATAPRAJA, 2020)
Amid the debate of whether community-based organizations created by the government can increase citizen participation in public affairs, by conducting a case study on Village Council formed by the DKI Jakarta Provincial Government, this research aimed to investigate the way this organization works and whether this organization can increase citizen participation. This study used a mixed method to achieve research objectives. The result indicated the minimal role of the Village Council in encouraging citizen participation. The ability of community organization to establish a quality relationship with citizens become a significant determining factor for inviting citizens to participate. However, it is not enough because the context of the existence of community organizations also determines the ability of community organizations to play their roles such as the construction of legal formal and construction of relationships built between a community organization and the arena of policymaking.